Innovation in Higher Education: Learning Styles and Effectiveness of Face-to-Face and Virtual Modalities in the Development of Human Talent - Liccioni, Edith Josefina; Manzo, Orlando Agustín Pérez; Laguna, Laura Sonia Contreras; Águila, Denisse Puentes (Journal of Posthumanism, 2025)
Higher education faces the challenge of training competent human talent in a globalized, changing and technologically mediated environment. This study examines the relationship between learning styles and the effectiveness of face-to-face and virtual modalities, analyzing their impact on the development of human talent. A mixed methodology was applied in Latin American university institutions, evaluating academic performance, perception of efficacy and the development of transversal competencies. The results suggest that innovative higher education must adapt to learning styles and strategically combine both modalities to maximize the student’s potential.